Application of Six Sigma in the procurement process in public institutions - Manosalvas Vaca, Carlos Anibal (2016)
Six Sigma is a methodology that focuses on improving quality in manufacturing and services companies demonstrating successful implementation. This article presents the results of implementing Six Sigma methodology for acquisitions process in an Ecuadorian public company. The application was made following the sequential steps of the methodology: define, measure, analyze, improve and control. In the first two stages, a diagnosis of the current situation was conducted, determining the critical variables. In the analysis stage, the process capability and control chart was calculated; and, through a principal component analysis, the tasks that cause greater variability in the process were determined. With the results obtained the best options for improvement were analyzed and chosen to design a system to implement and control the execution process.